[Rezension von: Egli, Werner, 1957-, The Sunuwār of Nepal and their sense of communication] - Wettstein, Marion (Zeitschrift für Ethnologie, 2017)
Wettstein reviews The Sunuwar of Nepal and their Sense of Communication: A Study in the Culture, Psychology and Shamanism of a Himalayan People by Werner M. Egli.
Gesehen am 16.10.2024
Keywords: Rezension